Cerebral Perfusion in Chronic Stroke: Implications for Lesion-Symptom Mapping and Functional MRI - Jessica D. Richardson; Julie M. Baker; Paul S. Morgan; Chris Rorden; L. Bonilha; Julius Fridriksson (Behavioural Neurology)
Lesion-symptom mapping studies are based upon the assumption that behavioral impairments are directly related to structural brain damage. Given what is known about the relationship between perfusion deficits and impairment in acute stroke, attributing specific behavioral impairments to localized brain damage leaves much room for speculation, as impairments could also reflect abnormal neurovascular function in brain regions that appear structurally intact on traditional CT and MRI scans. Compared to acute stroke, the understanding of cerebral perfusion in chronic stroke is far less clear. Utilizing arterial spin labeling (ASL) MRI, we examined perfusion in 17 patients with chronic left hemisphere stroke. The results revealed a decrease in left hemisphere perfusion, primarily in peri-infarct tissue. There was also a strong relationship between increased infarct size and decreased perfusion. These findings have implications for lesion-symptom mapping studies as well as research that relies on functional MRI to study chronic stroke.